Solar powered charge stations for electric vehicles. Issue 4 (26th November 2013) - Goldin, Erica; Erickson, Larry; Natarajan, Bala; Brase, Gary; Pahwa, Anil
<x xml:space="preserve">Abstract</x> Every hour, the sun emits more energy onto the Earth's surface than our entire world population uses in one year (Green Fuel, 2013, http://www.greenfuelsolar.com/solar‐fact‐or‐fiction/) Solar power provides us with the possibility of a cleaner and more renewable future. Global climate change as a result of greenhouse gases and the effects of low air quality caused by pollutants have become very substantial issues in our world today. The costs associated with greenhouse gas and air pollutant emissions, and the effect they have on human lives and human health, are major and growing concerns. The development and installation of solar powered charging stations will reduce the amount of greenhouse gases emitted into the atmosphere, future costs associated with climate change, and health issues. Thus, there is environmental, social, and economic value associated with the installation of solar powered charge stations. Solar powered charging stations have the potential of significantly reducing air pollutants and improving urban air quality. The electrification of transportation and the use of solar powered charging stations as an electricity source will improve people's quality of life. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 1298–1308, 2014